Detection of Vegetation Losses in Shrimp Farming Area Using Remote Sensing Technique. (Journal of Tropical Resources and Sustainable Science (JTRSS), 2019)
The conversion of mangrove forest to aquaculture activity leads to the destruction of habitat diversity and ecosystem. Shrimp farming is a sector of aquaculture that has a high potential for poverty alleviation and rural development in Tumpat, Kelantan. However, the development of this activity induces changes that potentially have negative impacts on the environment, one of which is vegetation deterioration. Pulau Terendak, Tumpat has been through the phase of conversion area which established as a shrimp farming area at year 1989. Using remote sensing technique, this study was implemented to identify the current status and total ranges of shrimp farming area by comparing vegetation losses from year 1989 to 2017. Land use and land cover maps of study area was analyzed through a process called image classification. Supervised classification using Maximum Likelihood algorithm was utilized to assess vegetation losses of the 45 hectare of shrimp farm area. Four main land use classes were detected namely water, bare area, dense vegetation and small vegetation. Result showed that in 25 years, vegetation of the area had decline to 23.3% while bare soil or open area increased to 8.5%. Digital analyzed data was compared to field verification procedure, accuracy assessment in this study was recorded at 64.3%. There are many causes for vegetation or mangrove loss but in this case the conversion of mangroves to shrimp farms has caused considerable attention whereby vegetation losses was found at serious state. Output of this study could suggest the authorities to plan a good strategy to address this issue in cost effective with maximum benefits for the environment and society.
Keywords: mangrove; land use and land cover; TM Landsat; coastal area